2019
DOI: 10.1002/fsn3.1164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arabinoxylan on colonic bacterial metabolites and mucosal barrier in high‐fat diet‐induced rats

Abstract: The aim of this study was to demonstrate the effect of arabinoxylan on colonic mucosal barrier and metabolomic profiles in high‐fat diet‐induced rats. A total of 20 six‐week‐old male rats were arranged randomly to two groups (n = 10/group), including a high‐fat diet (HFD) group and a high‐fat supplemented with arabinoxylan diet (AXD) group. Results showed that feeding AXD reduced serum lipopolysaccharide in rats after 5 weeks. In colonic digesta, Escherichia coli population was reduced, while Lactobacillus, Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…An hypocholesterolemic effect was also observed Lactobacillus paracasei M7 EPS in an in vitro model [ 106 ]. Several mechanisms have been proposed for the EPS activity, namely BS sequestration, deconjugation of BS and production of SCFA [ 107 , 108 , 109 , 110 ].…”
Section: Microbiota Bio-transformations Of Polysaccharides and Bile Salts: Hypocholesterolemic Implicationsmentioning
confidence: 99%
“…An hypocholesterolemic effect was also observed Lactobacillus paracasei M7 EPS in an in vitro model [ 106 ]. Several mechanisms have been proposed for the EPS activity, namely BS sequestration, deconjugation of BS and production of SCFA [ 107 , 108 , 109 , 110 ].…”
Section: Microbiota Bio-transformations Of Polysaccharides and Bile Salts: Hypocholesterolemic Implicationsmentioning
confidence: 99%
“…Furthermore, dietary fiber reduces transit time and increases satiety and intestinal motility. In addition to the immunomodulatory effects of polysaccharides, specifically arabinoxylan, a previous study showed that they regulate the level of lipopolysaccharides in the blood in the case of high-fat diets (Li et al, 2019).…”
Section: Analysis Of Microbial Communities With Different Substratesmentioning
confidence: 99%
“…Few studies have found increases in Lactobacillus with AX or AX-rich foods in a high-fat diet rat study [ 60 ], in two piglet feeding trials with AX from wheat (Naxus) [ 10 , 61 ], and in a double blinded, placebo-controlled, crossover human intervention study with AX-rich breakfast cereal intervention [ 62 ]. In contrast, another human intervention study consisting of wheat bran AX consumption showed no effect and even a decrease in Lactobacillus levels [ 63 ].…”
Section: Discussionmentioning
confidence: 99%